Palm gripper measurement device for post-stroke rehabilitation progressive tracking / Muhammad Najmi Hakim Nasir ... [et al.] - Nasir, Muhammad Najmi Hakim; Che Zakaria, Noor Ayuni; Othman, Nurul Atiqah; Johar, Khairunnisa; Mohd Mustafah, Nadia; Abd Halim, Azffanizam (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2024)
Various devices are used in the medical world to measure grip force. However, there is no well-defined method being used to quantify the distribution of grip forces applied by post-stroke patients. It is important to track the patient's progress in neurofeedback training throughout rehabilitation with quantitative evaluation. A palm gripper measurement device is being developed, equipped with Force Sensing Resistors (FSRs) (RP-S40-ST model) to capture grip force. The device provides valuable insights into rehabilitation progress by assessing the grip force. The analogue value from FSRs is linearly interpolated from the input range to the output range using the map function; 'map(avg_force, 0, 1023, 0, 15)' to scale the 'fsrReading' from the input range of 0 to 1023. The input range is converted into a score 0 to 15 scale of a bar graph to indicate the amount of force measured. The accuracy showed by Pearson's r shows a correlation trend between the analogue value and length of the bar graph with 0.97651 and 0.98083, respectively. A matrix was plotted for three subjects with different object sizes for device testing which shows the adjusted R2 is 0.955 highest for big objects and the lowest adjusted R2 is 0.63672 for small objects.